Kreativitas Guru Pendidikan Agama Islam Dalam Pembinaan Akhlak Siswa Di SMK Negeri 2 Jombang - Pangestu, Ariyanti; Rozaq, Abd (LP3M STIT Al Urwatul Wutsqo Jombang, 2023)
Teacher creativity is one of the most important factors that can encourage students to be more active in learning. Student moral development is being able to distinguish between what is good and what is bad according to reason and the norms that exist in the environment where students are. The aims of this thesis are: (1) The form and process of creativity of Islamic religious education teachers at SMK Negeri 2 Jombang (2) How the morals of students at SMK Negeri 2 Jombang are. This research uses a qualitative approach. Methods of data collection is done through interviews, observation and documentation. The data analysis technique used is data reduction, data display and verification. The results of the study showed that (1) the creative form of Islamic religious education teachers in developing student morals begins with a handshake, Duha prayer, greetings, tawassul and reading Juz amma one letter. The creative process of Islamic religious education teachers in fostering student morals at SMK Negeri 2 Jombang (a) Providing examples of good habits (b) Applying good attitudes or morals and implementing the formation of character in daily activities. (2) Student morals in SMK Negeri 2 Jombang. The method of fostering morals is (a) fostering student morals (b) habituation (c) daily motivation. The conclusion of this study is that the creativity of Islamic religious education teachers in fostering student morals at SMK Negeri 2 Jombang plays a positive role in changing the attitudes of their students. From this study it proves that many students' attitudes have changed for the better from several aspects such as morals to Allah SWT, morals towards teachers, morals towards parents, morals towards friends, morals towards themselves and morals towards the environment because of the role of Islamic Religious Education teachers.